Current issues, desired changes, and future trends: opinions of strength and conditioning coaches in professional soccer and cricket. - Weldon, A.; Duncan, A.; Turner, A. (Journal of Australian Strength and Conditioning, 2020)
Irrespective of the sport, common goals of a SCC include reducing injuries, while optimizing physical and sporting performance. Various literature advises the practices of SCCs, however comparatively little is known on their opinions. Therefore, this study investigated the opinions of SCCs regarding current issues, desired changes and future trends in strength and conditioning.